The effect of Mentorship Program on Self-Esteem, Anxiety and Learning Clinical Skills of Emergency Medical Students: A Randomized Controlled Trial - Hamideh Mashalchi; Ferdos Pelarak; Somayeh Mahdavi Kian; Tayebeh Mahvar; Amin Abdolvand; Morteza Habibi Moghadam (Hamadan University of Medical Sciences, 2021)
Background and Objective: Clinical education (mentorship program) is one of the most important aspects of education in the medical sciences. Therefore, this study was conducted to investigate the effect of mentorship program on self-esteem, anxiety and learning clinical skills of emergency medical students. Material and Methods: This study was a quasi-experimental study in which 24 emergency medical students of Dezful University of Medical Sciences were enrolled by available sampling. Data collection scales were Coopersmith Self-Esteem Inventory, Spielberger State-Trait Anxiety Inventory and Clinical Skills Questionnaire. Data analysis was performed using SPSS-20 software and descriptive and analytical statistics. Results: In this study, 70.8% of students (17 persons) got an average point of 15-17 and were 21 years old. Also, the mean scores of self-esteem (P <0.001), anxiety (P <0.001) and clinical skills (P <0.001) before and after clinical training were significantly different so that the mean of self-esteem, anxiety and clinical skills of students before Clinical education were 37.12, 90.29 and 112.29, followed by 46.92, 70.50 and 136, respectively. Conclusion: After using the mentorship program, an increase in clinical skills, a decrease in anxiety and an increase in students' self-esteem were observed. Therefore, it is necessary to develop a clinical education program that provides a path for scientific growth to acquire clinical competencies.